Leucyl-tRNA synthetase from Thermus thermophilus. Purification and some properties of the crystallizing enzyme - Yaremchuk, A.D.; Gudzera, O.I.; Egorova, S.P.; Rozhko, D.I.; Kriklivy, I.A.; Tukalo, M.A. (Біополімери і клітина, 2001)
Leucyl-tRNA synthetase from Thermus thermophilus (LeuRSTT) was purified to homogeneity using a five-step purification procedure. The enzyme was characterized and crystallized. Molecular mass determinations of the native and denatured proteins indicate monomeric structure of LeuRSTT with the molecular mass of about 101 kDa. The protein obtained is remarkably thermostable and retains 97 % of its initial aminoacylation activity after 1 hour of incubation at 88 °C. Crystals of LeuRSTT were obtained from ammonium sulfate solution by the vapour diffusion techniques. The crystals quality was improved by crystallization from the precipitate. Лейцил-тРНК синтетаза из Thermus thermophilus (ЛейРСТТ) выделена в гомогенном состоянии с использованием пяти стадий очистки. Фермент охарактеризован и получены его кристаллы. Определена молекулярная масса нашивного и денатурированного белка. Установлено, что ЛейРСТТ представляет собой мономер с молекулярной массой 101 кДа. Полученный фермент обладает значительной термостабильностью и сохраняет 97 % аминоацилирующей активности после инкубации в течение 1 ч при температуре 88 °С. Кристаллы ЛейРСТТ получены методом диффузии паров с использованием в качестве осадителя раствора сульфата аммония Лейцил-тРНК синтетазу із Thermus thermophilus (ЛейРСТТ) виділено в гомогенному стані з використанням п'яти стадій очищення. Фермент охарактеризовано та отримано його кристали. Визначено молекулярну масу нативного і денатурованого білка. Встановлено, що ЛейРСТТ являє собою мономер з молекулярною масою 101 кДа. Отриманому ферментові притаманна значна термостабільність і він зберігає 97 % аміноацилюючої активності після інкубації протягом 1 год при температурі 88 ° С Кристали ЛейРСТТ одержано методом дифузії парів із використанням як осаджувана розчину сульфату амонію.